Use of horse riding in chronic pain therapy - Mazur, Sylwia; Mazur, Agata; Madera, Magdalena; Bizan, Aleksy; Nagórska, Emilia; Marcinkowski, Krzysztof; Strus, Karolina; Kublińska, Aleksandra; Zdunek, Roksana; Dąbrowska, Natalia (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Chronic pain is a struggle itself and also a symptom in many common conditions. Its complexity requires diverse treatment methods including some that might seem unconventional, for example, horse riding. This study gathers information about the use of equine assisted therapy in pain relief. Brief description of the state of knowledge: Hippotherapy is known as an important part of care for patients with cerebral palsy, attention deficit and autism. The rhythmical, multidimensional movements of the horse are transmitted to the rider’s pelvis and help in strengthening and stretching the muscles which result in better posture stabilization and balance. The positive effects of equine assisted therapy are not limited to only physical ones but positive social, cognitive and psychological effects can be observed as well. In order to lower the cost and time of the therapy, horse riding simulators were invented. So far, horse riding has been tested as a pain relief tool in entities like nonspecific low back pain, multiple sclerosis and arthritis. Summary: Horse riding sessions had beneficial effects on pain levels among patients with nonspecific back pain and arthritis. There is a need to conduct further research in order to properly compare the use of real horses versus horse simulators. Hippotherapy was well perceived by different patient groups so maybe it has the potential to be an important part of pain management in various conditions.